Parenteral nutrition-associated liver complications in children - Btaiche, Imad F. (2002)
Parenteral nutrition is a life-saving therapy for patients with intestinal failure. It may be associated with transient elevations of liver enzyme concentrations, which return to normal after parenteral nutrition is discontinued. Prolonged parenteral nutrition is associated with complications affecting the hepatobiliary system, such as cholelithiasis, cholestasis, and steatosis. The most common of these is parenteral nutrition-associated cholestasis (PNAC), which may occur in children and may progress to liver failure. The pathophysiology of PNAC is poorly understood, and the etiology is multifactorial. Risk factors include prematurity, long duration of parenteral nutrition, sepsis, lack of bowel motility, and short bowel syndrome. Possible etiologies include excessive caloric administration, parenteral nutrition components, and nutritional deficiencies. Several measures can be undertaken to prevent PNAC, such as avoiding overfeeding, providing a balanced source of energy, weaning parenteral nutrition, starting enteral feeding, and avoiding sepsis.